Proceedings of the 2018 International Conference on Quantitative InfraRed Thermography 2018
DOI: 10.21611/qirt.2018.054
|View full text |Cite
|
Sign up to set email alerts
|

Systematic errors in the evaluation of uncorrected data from thermographic lock-in measurements

Abstract: Lock-in thermography (LT) is based on the correct evaluation of phase differences between the temperature oscillations at different surface regions of the object under test during periodic heating. Since the usual heating procedures contain a DC component, the actual heating pattern achieved is not harmonic. This causes systematic deviations when phase differences are determined by means of harmonic analysis, e.g. with FFT analysis. The resulting errors depend clearly on the ratio between DC and AC amplitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The surface temperature of the cylinder coating is measured 5 s for each excitation frequency. However, well known systematic errors during lock in thermography result from lock in measurements during early non linear heating of the sample [23]. To avoid non linear sample heating during the actual measurements, the cylinder coating is pre heated in advance of each measurement for additional 5 s at each ex citation frequency.…”
Section: Lock In Systemmentioning
confidence: 99%
“…The surface temperature of the cylinder coating is measured 5 s for each excitation frequency. However, well known systematic errors during lock in thermography result from lock in measurements during early non linear heating of the sample [23]. To avoid non linear sample heating during the actual measurements, the cylinder coating is pre heated in advance of each measurement for additional 5 s at each ex citation frequency.…”
Section: Lock In Systemmentioning
confidence: 99%
“…However, to even further minimize the influence of lateral heat flow, temperature values are only evaluated within a spot diameter of 6.7 mm, since lateral heat diffusion dominantly occurs in the outer region of the excited area. Following recommendations by Krankenhagen et al [38], the sample is preheated for 5 s in advance of every applied frequency to avoid non-linear sample heating during early excitation. Preliminary experiments have shown that this time scale is sufficient to eliminate non-linear heating effects for all applied modulation frequencies.…”
Section: Thermal Wave Interferometry (Twi)mentioning
confidence: 99%